Aesthetic reconciliation with the self-evidence of death and its problem in Vladimir Jankélévitch - Talbi, Kamir (The International tax journal, 2026)
Philosophical discourse has often tended to regard death as an event occurring within the very unfolding of life, both being seen as a dual-pole necessity, each referring to the other. As Louis Lavelle states: “If death gives meaning to life, then life, in turn, gives us the capacity to experience it, or rather, grants us the experience of death.” Thus, the idea of life can only acquire its significance through the haunting presence of death that accompanies it. However, in the conception of Ludwig Wittgenstein, the experience of death cannot be lived, and it is therefore impossible to speak of any horizon beyond experience. This is precisely the issue raised by Vladimir Jankélévitch, who sought to elevate the idea of death understood as an evident event and a trivial ordinary fact to the level of a genuine philosophical problem. For thinking about death is not only the concern of philosophy but its unavoidable destiny.